2005
DOI: 10.1038/sj.npp.1300836
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy of Striatal and Extrastriatal Dopamine D2/D3 Receptors by Olanzapine and Haloperidol

Abstract: There have been conflicting reports as to whether olanzapine produces lower occupancy of striatal dopamine D 2 /D 3 receptor than typical antipsychotic drugs and preferential occupancy of extrastriatal dopamine D 2 /D 3 receptors. We performed [18 F] fallypride PET studies in six schizophrenic subjects treated with olanzapine and six schizophrenic subjects treated with haloperidol to examine the occupancy of striatal and extrastriatal dopamine receptors by these antipsychotic drugs. [18 F] setoperone PET studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 53 publications
2
63
2
1
Order By: Relevance
“…As reported by Schotte et al (1996), these agents, including clozapine, risperidone, 9-hydroxyrisperidone (paliperidone), olanzapine, pipamperone, quetiapine, sertindole, ziprasidone, and zotepine, also have higher occupancy in the rat cortex and striatum of 5-HT 2A than D 2 receptors, respectively, at all but the highest doses studied. PET studies are also consistent with the view that at clinically relevant doses, those agents, which are direct acting antagonists of D 2 receptors, have higher occupancy of D 2 than 5-HT 2A receptors (Goyer et al, 1996;Nyberg et al, 1999;Gefvert et al, 2001;Kessler et al, 2005). Aripiprazole, a partial D 2 receptor agonist, has a higher D 2 than 5-HT 2A receptor occupancy at clinical doses, but, nevertheless, has a weak functional effect to inhibit D 2 receptor stimulation (Mamo et al, 2007).…”
Section: Da Effluxsupporting
confidence: 67%
“…As reported by Schotte et al (1996), these agents, including clozapine, risperidone, 9-hydroxyrisperidone (paliperidone), olanzapine, pipamperone, quetiapine, sertindole, ziprasidone, and zotepine, also have higher occupancy in the rat cortex and striatum of 5-HT 2A than D 2 receptors, respectively, at all but the highest doses studied. PET studies are also consistent with the view that at clinically relevant doses, those agents, which are direct acting antagonists of D 2 receptors, have higher occupancy of D 2 than 5-HT 2A receptors (Goyer et al, 1996;Nyberg et al, 1999;Gefvert et al, 2001;Kessler et al, 2005). Aripiprazole, a partial D 2 receptor agonist, has a higher D 2 than 5-HT 2A receptor occupancy at clinical doses, but, nevertheless, has a weak functional effect to inhibit D 2 receptor stimulation (Mamo et al, 2007).…”
Section: Da Effluxsupporting
confidence: 67%
“…The quetiapine study (Stephenson et al, 2000) used the same methodology criticized by Olsson (Olsson and Farde, 2001). In a study of olanzapine-treated schizophrenic patients, we have reported no preferential occupancy of cortical DA D 2 r but sparing of nigral DA D 2 r occupancy using the same methods utilized here (Kessler et al, 2005).…”
Section: Introductionmentioning
confidence: 71%
“…The substantia nigra can be stereotactically localized in the ventral midbrain 9-14 mm below the ACPC line (Schaltenbrand and Wahren, 1977) and can be easily visualized in the midbrain on PET [ 18 F]fallypride scans (see Figure 2). The amygdala can be easily visualized in the anteromedial temporal lobe on MRI scans just anterior to the tip of the temporal horn of the lateral ventricle and deep to the uncus (Kessler et al, 2005); stereotactically, the amygdala is localized approximately 6-20 mm below the ACPC line, from 12 to 28 mm lateral to the midline, and from 2 to 12 mm behind the plane of the anterior commissure (Schaltenbrand and Wahren, 1977). To decrease partial voluming from the striatum, regions of interest for the amygdala were drawn on the MRI images from 10 to 16 mm below the plane of the ACPC.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…For example, risperidone shows no or little separation between 5-HT 2A and D 2 RO, depending on the dose, with ≥78 % occupancy of 5-HT 2A receptors and ≥75 % occupancy of D 2 receptors at a 6 mg/day dose and approximately 83 % 5-HT 2A RO and 72 % D 2 RO at a dose of 3 mg/day Nyberg et al 1999). Olanzapine also shows little separation between 5-HT 2A RO (68-78 %) and striatal D 2 RO (85-93 %; Kessler et al 2005). These atypical antipsychotic drugs with relatively high striatial D 2 RO elevate prolactin levels (Bushe et al 2008) and can induce extrapyramidal motor side effects (extrapyramidal symptoms (EPS)) at therapeutic doses (Rummel-Kluge et al 2012).…”
Section: Introductionmentioning
confidence: 99%